The interaction of neuroimmunology, neuromodulator, and neurotransmitter with nociceptor and MAPK signaling - Dewi, Dewa Ayu Mas Shintya; Wiryana, Made (Bali Journal of Anesthesiology, 2019)
ABSTRACTPhysiological pain is a protection mechanism against tissue damage or potential tissue damage. Inflammation pain is followed by tissue damage due to temperature, mechanical and chemical stimuli which increase crosstalk between neuron nociceptor, immune system, neuromodulator and neurotransmitter, and MAPK (Mitogen Activating Protein Kinase) signal. Initially, immune cell is produced at the primary afferent nerve endings and spinal cord, modulate thermal sensitivity and mechanic through MAPK signaling, then neuromodulator and neurotransmitter at the afferent nerve endings will regulate the innate immune response, adaptive and vascular